A Feasibility and Acceptability Trial of Social Cognitive Therapy in Early Psychosis Delivered Through a Virtual World: The VEEP Study - Thompson, Andrew; Elahi, Farah; Realpe, Alba; Birchwood, Max; Taylor, David; Vlaev, Ivo; Leahy, Fiona; Bucci, Sandra (Frontiers in Psychiatry, 2020)
Background Addressing specific social cognitive difficulties is an important target in early psychosis and may help address poor functional outcomes. However, structured interventions using standard therapy settings including groups suffer from difficulties in recruitment and retention. Aims To address these issues, we aimed to modify an existing group social cognitive intervention entitled ‘Social Cognition and Interaction Training' (SCIT) to be delivered through a virtual world environment (Second Life ©). Methods A single arm nonrandomized proof-of-concept trial of SCIT-VR was conducted. Five groups of three to five individuals per group were recruited over 6 months. Eight sessions of SCIT-VR therapy were delivered through the virtual world platform Second Life© over a 5-week intervention window. Feasibility was examined using recruitment rates and retention. Acceptability was examined using qualitative methods. Secondary outcomes including social cognitive indices, functioning, and anxiety were measured pre- and postintervention. Results The SCIT-VR therapy delivered was feasible (36% consent rate and 73.3% intervention completion rate), acceptable (high overall postsession satisfaction scores) and safe (no serious adverse events), and had high levels of participant satisfaction. Users found the environment immersive. Prepost changes were found in emotion recognition scores and levels of anxiety. There were no signs of clinical deterioration on any of the secondary measures. Conclusion This proof-of-concept pilot trial suggested that delivering SCIT-VR through a virtual world is feasible and acceptable. There were some changes in prepost outcome measures that suggest the intervention has face validity. There is sufficient evidence to support a larger powered randomized controlled trial. Clinical Trial Registration ISRCTN, identifier 41443166